REFORMASI PAJAK DALAM RANGKA MENINGKATKAN PENDAPATAN NEGARA - Niru Anita Sinaga (JURNAL ILMIAH HUKUM DIRGANTARA, 2017)
Abstract:One of the goals of the state of Indonesia lies in the Preamble of the 1945 Constitution of the State of the Republic of Indonesia, namely shall protect the whole Indonesian nation and the entire native land of Indonesia and to advance the public welfare, to educate the life of the nation, and the participate in the execution of world order which is by virtue of freedom. One of the way to make it happen is through development in all fields equally both materially and spiritually. Development requires funds, one source through tax collection. Tax is a mandatory contribution to the state that is owed by an individual or entity that is compelling based on law, by not obtaining direct remuneration and used for the purposes of the state for the greatest possible prosperity of the people. In general tax functions: Financially, regulate, stability, and redistribution of funding. The principle and theory of tax collection, among others: Justice, legal philosophy, economics, and finance. Terms of tax collection must meet the requirements of justice, juridical, economic, financial and the collection system should be simple. In order for tax collection to work properly, regulations on taxation have been established. But in practice often experience problems. The discussion in this study is to discuss about: "What factors influence state revenue from the taxation sector in Indonesia is not optimal" and "How the government efforts to increase state revenues from the taxation sector" The method used is normative juridical. State revenues can be increased by reforming the taxation sector to make changes to the tax system significantly and comprehensively covering the revamping of tax administration, improvement of tax regulations, and increasing tax base. In the event of a dispute concerning taxation, it shall be settled in accordance with the provisions and principles of tax law.Keywords: Tax, Tax Reform Abstrak :Salah satu tujuan negara Indonesia terdapat pada Pembukaan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Alinea IV, yakni melindungi segenap bangsa Indonesia dan seluruh tumpah darah Indonesia, memajukan kesejahteraan umum, mencerdaskan kehidupan bangsa dan ikut melaksanakan ketertiban dunia. Salah satu cara untuk mewujudkannya adalah melalui pembangunan di segala bidang secara merata baik materiil maupun spritual.   Pembangunan memerlukan dana, salah satu sumbernya melalui pemungutan pajak. Pajak adalah kontribusi wajib kepada negara yang terutang oleh orang pribadi atau badan yang bersifat memaksa berdasarkan undang-undang, dengan tidak mendapatkan imbalan secara langsung dan digunakan untuk keperluan negara bagi sebesar-besarnya kemakmuran rakyat. Secara umum fungsi pajak: Finansial, mengatur, stabilitas, dan redistribusi pendanaan. Asas dan teori pemungutan pajak, antara lain: Keadilan, falsafah hukum, ekonomi, dan finansial. Syarat pemungutan pajak harus memenuhi syarat keadilan, yuridis, ekonomis, finansial dan sistem pemungutannya harus sederhana. Agar pemungutan pajak dapat berjalan dengan baik telah dibentuk peraturan-peraturan di bidang perpajakan. Namun dalam pelaksanaannya sering mengalami permasalahan. Pembahasan dalam penelitian ini adalah membahas tentang: “Faktor-faktor apa yang mempengaruhi tidak maksimalnya pendapatan negara dari sektor pajak di Indonesia” dan “Bagaimana upaya pemerintah untuk meningkatkan pendapatan negara dari sektor perpajakan” Metode yang digunakan adalah yuridis normatif. Penerimaan negara dapat ditingkatkan dengan melakukan reformasi dibidang perpajakan yaitu melakukan perubahan system perpajakan secara signifikan dan komprehensif yang mencakup pembenahan administrasi perpajakan, perbaikan regulasi perpajakan, dan peningkatan basis pajak. Apabila terjadi sengketa mengenai perpajakan, harus diselesaikan sesuai dengan ketentuan-ketentuan dan asas-asas hukum pajak. Kata kunci: Pajak, Reformasi Pajak